Originally Posted by

**duckduckgoose33** The problems is:

One factor of x^3 + 2x^2 - 23x - 60 is (x=4). Find the remianing factors.

I tried to group them and factor but the second binomial wouldn't factor.

They tell you x=4 is a solution,

But that is not true!

Perhaps you mean x=-4

That means

(x-(-4))=(x+4)

Is a factor.

Thus, use long division,

Code:

x^3 + 2x^2 - 23x - 60 : x + 4=x^2 - 2x-15
x^3 + 4x^2
-------------
-2x^2 - 23x - 60
-2x^2 - 8x
------------
-15x - 60
-15x - 60
----------
0

Now we need to factor,

x^2-2x-15

Which factors as,

(x-5)(x+3)

Thus, the full factorization is,

(x-5)(x+3)(x+4)